Analisis Pengaruh Etos Kerja, Kepemimpinan Partisipatif dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Kantor Kecamatan Alor Barat Laut Kabupaten Alor - Jeniver Olivia Aring (Peneliti.net, 2023)
Performance is the result of work achieved by employees based on job requirements. A job has certain requirements so that it can be carried out to achieve goals which are also known as work standards. The results of work are things that are obtained by an employee in carrying out the work according to the requirements or performance standards. An employee is said to be successful in carrying out his work or having good performance, if the work results obtained are higher than the performance standards. To know this, it is necessary to evaluate the performance of each employee in an agency. Performance problems certainly can not be separated from the process results and usability. Performance itself means a work result that can be achieved by a person or group of people in an organization, according to their respective authorities and responsibilities, in order to achieve organizational goals. This study aims to determine the effect of work ethic, participatory leadership and work environment on employee performance at the Alor Barat Laut District Office, Alor Regency, both partially and simultaneously. This type of research is quantitative research with data collection techniques, namely observation, interviews, and documentation studies. This study uses population primary data and samples are employees at the Alor Barat Laut District Office, Alor Regency, totaling 22 people. And the sampling technique in this study is a saturated sample. The statistical method used in this study is multiple linear regression. The results of this study indicate that: (1). the work ethic variable affects the performance of employees at the Alor Barat Laut District Office, Alor Regency. This is evidenced by the significance value of the t test of 0.001 or 0.1% where this value is smaller than the alpha value of 0.05 or 5%. (2). variable Participatory Leadership has a positive effect on employee performance at the Alor Barat Laut District Office, Alor Regency. This is evidenced by the significance value of the t test of 0.004 or 0.4% where this value is smaller than the alpha value of 0.05 or 5%. (3). Work Environment variables have a positive effect on employee performance at the Alor Barat Laut District Office, Alor Regency. This is evidenced by the significance value of the t test of 0.024 or 2.4% where this value is smaller than the alpha value of 0.05 or 5%. (4). simultaneously variable work ethic. Participatory leadership and work environment have a positive effect on employee performance at the Alor Barat Laut District Office, Alor Regency. This is evidenced by the significant value of the F test of 0.000 or 0.00% where this value is smaller than the alpha value which is equal to 0.05 which is 5%. (5) variable work ethic. Participatory leadership and work environment have an effect on employee performance by 76.6%. while the remaining 23.4% is influenced by other factors that have not been examined in this study.